Protective effect of L-carnitine nanoparticles Vs carnitine on lead acetate-induced toxicity in male rats. - Hayder Talib Mahdi; Rashad Fadhil Ghadhban (Journal of Advanced Biotechnology and Experimental Therapeutics, 2022)
Chitosan nanoparticles are important materials that are widely used in many biological, engineering and food industries and are also used as plant growth stimulants as well as use as vectors for drug delivery to target cells. Whereas L-carnitine (LC) is a water-soluble compound that contributes to the transport of long-chain fatty acids across the mitochondrial membranes and the oxidation of β-lipids. Methods: 60 male rats (Rattus Rattus) were divided into six equal groups. The first group (control group): Animals received orally distilled water. The second group. Animals received 1ml orally lead acetate at a dose of 30 mg/kg of body weight daily for 30 days. Third group: Animals received 1ml (lead acetate 30mg/kg B.W + L-carnitine (100mg/ kg B.W. /daily). The fourth group. Animals received 1ml (lead acetate 30mg/kg B.W. + Nano L-carnitine 100mg/ kg B.W./ daily). The fifth group: Animals received 1ml of L-Carnitine orally at a dose of 100mg/ kg B.W /daily. The sixth group: Animals received 1ml of L-Carnitine-NPs orally at 100mg/ kg B.W /daily. Results: Our findings demonstrated that exposure to lead acetate caused a significant increase in liver-enzymes Aspartate Transaminase (AST), Alanine Transaminase (ALT), and Alkaline Phosphatase (ALP) and renal function enzymes (creatinine and urea) in the lead acetate group. Whereas, lead treatment increased oxidative stress and reactive oxygen species (ROS), which can be removed through decreased glutathione (GHPX) and increased malondialdehyde (MDA). Conclusions: Histopathological study showed significant changes in the brain (cerebellum) that disrupted the normal arrangement of the three layers, with large distances between the Purkinje cell layer and the molecular or granular layer. According to the study, we can conclude that the Nano L-Carnitine had a greater role in protecting against the effect of lead at the haematological parameters and a clear role in the protection against histopathology change of lead poisoning. L-Carnitine and Nano L-Carnitine had an active ...